1990
DOI: 10.1083/jcb.111.3.1027
|View full text |Cite
|
Sign up to set email alerts
|

Brain dynein (MAP1C) localizes on both anterogradely and retrogradely transported membranous organelles in vivo.

Abstract: Abstract. Brain dynein is a microtubule-activatedATPase considered to be a candidate to function as a molecular motor to transport membranous organdies retrogradely in the axon. To determine whether brain dynein really binds to retrogradely transported organelles in vivo and how it is transported to the nerve terminals, we studied the localization of brain dynein in axons after the ligation of peripheral nerves by light and electron microscopic immunocytochemistry using affinity-purified anti-brain dynein anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
156
0
2

Year Published

1993
1993
2011
2011

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 249 publications
(175 citation statements)
references
References 54 publications
17
156
0
2
Order By: Relevance
“…In fact, kinesin is primarily associated with anterogradely moving membranous organelles in the axon, strongly supporting the hypothesis that kinesin is really an anterograde motor in vivo (8). Brain dynein is associated with both anterogradely and retrogradely moving membranous organelles (9), consistent with the suggestion that brain dynein is transported to the nerve terminal by fast flow and subsequently functions as a retrograde transport motor in vivo. Molecular genetic and ultrastructural approaches have dissected the molecular structure and functional domains of kinesin motors (10)(11)(12).…”
supporting
confidence: 74%
“…In fact, kinesin is primarily associated with anterogradely moving membranous organelles in the axon, strongly supporting the hypothesis that kinesin is really an anterograde motor in vivo (8). Brain dynein is associated with both anterogradely and retrogradely moving membranous organelles (9), consistent with the suggestion that brain dynein is transported to the nerve terminal by fast flow and subsequently functions as a retrograde transport motor in vivo. Molecular genetic and ultrastructural approaches have dissected the molecular structure and functional domains of kinesin motors (10)(11)(12).…”
supporting
confidence: 74%
“…To elucidate KIF2's dynamics within axons, we observed its localization after ligating the peripheral (saphenous) nerves of adult mice. Our previous research has demonstrated that anterogradely and retrogradely transported membranous organelles, respectively, accumulate at the proximal and distal region of the ligated portion (Hirokawa et al, 1990. After 20 h of ligation, the KIF2 polyclonal antibody strongly stained the proximal region, though much less so the distal one (Fig.…”
Section: Localization Of Kif2 In Ligated Peripheral Nervesmentioning
confidence: 74%
“…These motors simultaneously bind to their cargo, which was shown in various cell systems, including fish and frog melanosomes (37), amoebas (38), lipid droplets in flies (14), intraflagellar transport in worms and algae (39,40), and vesicles in mammalian axons (41,42). The concurrent presence of kinesin and dynein is thought to be crucial for motor activity (3,13,43), but also recycles the motor back to MT plus ends (39,41). In fungi, kinesin-1 is thought to be involved in this process (26,30), making it likely that the observed anterograde motility of dynein is due to kinesin-1 activity.…”
Section: Discussionmentioning
confidence: 99%
“…In fungi, kinesin-1 is thought to be involved in this process (26,30), making it likely that the observed anterograde motility of dynein is due to kinesin-1 activity. It remains to be seen whether both motors directly interact (42) or attach to the same membranous cargo (41).…”
Section: Discussionmentioning
confidence: 99%